Potency and Safety of G12C Inhibitors in Solid Tumors: A Systematic Review - Sara El Zaitouni; Abdelilah Laraqui; Youssra Boustany; Soukaina Benmokhtar; Hicham El Annaz; Rachid Abi; Mohamed Rida Tagajdid; Safae El Kochri; El Arbi Bouaiti; Idriss Lahlou Amine; Rabii Ameziane El Hassani; Khalid Ennibi (Clinical Medicine Insights: Oncology)
Background: The Kirsten rat sarcoma viral oncogene homolog (KRAS) gene, specifically the cysteine residue mutation KRAS (G12C), has garnered significant attention as a therapeutic target for solid cancer patients with KRAS mutations. Despite this interest, the efficacy and safety profiles of KRAS G12C inhibitors remain incompletely understood. In this study, we comprehensively evaluate the effectiveness and toxicity of relevant KRAS G12C inhibitors (Sotorasib, Adagrasib, Garsorasib, and Divarasib) in patients with colorectal cancer (CRC), non-small-cell lung cancer (NSCLC), and pancreatic ductal adenocarcinomas (PDAC). Methods: Our systematic review is guided by Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. We review the available clinical trials data on KRAS G12C inhibitors in KRAS G12C-mutated solid tumors. We searched PubMed, EMBASE, Cochrane Library, and major international conferences for clinical trials from January 2020 until August 2023. Results: A total of 17 eligible studies were included. KRAS G12C inhibitions with Sotorasib (41.2%) and Adagrasib (41.2%) each of them were reported in 7 studies. Divarasib was reported in 2 studies (11.8%) and Garsorasib was reported in 1 study (6.7%). Sotorasib showed a significant clinical benefit in terms of objective response rate (ORR) (7.1%-47%), progression-free survival (PFS) (4-6.8 months), and overall survival (OS) (4-24 months); it is more efficient in NSCLC patients with an OS of 2 years, PFS of 6.3 months, and an ORR of 41%. Adagrasib also showed significant clinical activity with an ORR (19%-53%), PFS (3.3-11.1 months), and OS (10.5-23.4 months), with more effectiveness in NSCLC patients with an OS of 23.4 months, PFS of 11.1 months, and an ORR of 53.3%. Adagrasib is more efficient with an ORR of 35.1%, PFS of 7.4 months, and an OS of 14 months in patients with PDAC, than Sotorasib which showed an ORR of 21%, PFS of 4 months, and an OS of 6.9 months. However, Adagrasib and Sotorasib are moderately efficient in CRC clinical trials. Conclusion: This study confirms that patients treated with these KRAS G12C inhibitors, exclusively or combined with conventional therapies, achieve better treatment responses and modulate the progressions of these solid tumors.